Historicizing the Enlightenment. Volume 1, Politics, Religion, Economy, and Society in Britain - McKeon, Michael, 1943- (Lewisburg, Pennsylvania : Bucknell University Press, 2023)
"The Enlightenment has been linked to some of the most powerfully destructive developments of modern life: imperialism, racism, capitalist exploitation, scientific absolutism, totalitarian rule; and behind these developments, the domination of facts over values, quantity over quality, the abstract over the concrete, reason over humanity, division over connection. In this two-volume collection of career-spanning essays, influential literary critic Michael McKeon argues a more complicated view by practicing a different way of doing history: imagining these oppositions as the product not of the Enlightenment but of modern experience in its maturity. These essays conjure what it was like to live through the emergence of concepts and practices that are now commonplace-society, privacy, the public, the market, secularity, democracy, human rights, sex and gender, fiction, the aesthetic attitude. Volume 1 emphasizes the revolutionary break with tradition enacted by the British Enlightenment and the effects of its inversion of traditional hierarchies. With specific focus on economics and politics, religion and society, this collection amplifies the remarkable contribution McKeon has made to the intellectual history of the Enlightenment, and is an essential addition to any collection. Published by Bucknell University Press. Distributed worldwide by Rutgers University Press"--
Frontmatter -- Contents -- Introduction -- 1. Tradition as Tacit Knowledge -- 2. Civil and Religious Liberty: A Case Study -- 3. Virtual Reality -- 4. Gender and Sex, Status and Class -- 5. Biography, Fiction, Personal Identity -- 6. Historical Method -- Acknowledgments -- Notes -- Source Notes -- Index -- About the Author
Description based upon print version of record.
JSTOR
Keywords: Great Britain -- Intellectual life -- 18th century; Enlightenment -- Great Britain; Great Britain -- Civilization -- 18th century; Grande-Bretagne -- Vie intellectuelle -- 18e siècle.; Siècle des Lumières -- Grande-Bretagne.; Grande-Bretagne -- Civilisation -- 18e siècle.; HISTORY / General; Civilization; Enlightenment; Intellectual life; Great Britain; 1700-1799; Dialectics, Parody, Virtual reality, Secularization, Periodization, The public sphere, The aesthetic, Sex and gender, Separate spheres, Homosexuality, Class consciousness, Class, Biography, Fiction, Identity, Historicizing, Historical Method, Civil liberty, Religious liberty, Tradition, Knowledge, Enlightenment, Enlightenment thought, British Enlightenment, Reason, Karl Marx, Friedrich Engels, Marxism, Max Horkheimer, Theodore Adorno, Michel Foucault, Francis Bacon, Jürgen Habermas, Georg Wilhelm Friedrich Hegel, Civil society, Print culture, Realism, Domestication, Imitation, Conjectural history, Commodity fetishism; Electronic books